KONFLIK SOSIAL DI DISTRIK NABIRE, KABUPATEN NABIRE, PROVINSI PAPUA - Mesak Uti; Romi Mesra; Yoseph D.A Santie (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
The purpose of this study was to identify the forms and impacts of social conflict in the Nabire District, Nabire District, Papua Province. This study used a qualitative research method with observation and interview data collection methods. Data analysis uses 3 stages, namely data reduction, data presentation and drawing conclusions. The results of this study indicate that the forms of conflict that occurred in Nabire District were conflicts that occurred in schools between students and land conflicts that occurred within the community. The impact of conflicts between students in schools has a very small scale and is not widespread, while land conflicts that occur between indigenous tribes and migrants and other tribes in Papua are conflicts that are difficult to resolve